The Influence of Employee Placement, Training, and Organizational Culture on Employee Performance - Pancasasti, Ranthy (PT Larva Wijaya Penerbit, 2023)
Backgrounds: Performance is a work achieved by a person in carrying out the tasks assigned to him based on skills, experience and sincerity and time. Performance is related to a number of factors, including Employee Placement, Training, and Organizational Culture. Training is one of the factors that can shape a person's performance, while the benefits of placement are to form The Right Man on the Right Place, Time and Job. Organizational culture is important as a moral and value reference in carrying out tasks. Purpose: The purpose of this study was to measure the effect of Employee Placement, Training and Organizational Culture on Employee Performance at Perusahaan XXX Banten Banten. Originality/values: The novelty in this research is that it has not been found in previous studies that discuss the magnitude of the influence of Employee Placement, Training, Training and Organizational Culture on Employee Performance at Perusahaan XXX Banten Banten. Research limitations: The limitation in this study is to measure the influence of employee placement, training and organizational culture on employee performance at Perusahaan XXX Banten Banten. Design/methodology/approach The method used in this research is descriptive quantitative method with the help of a questionnaire with an interval scale of 1-10 points. The population in this study were all employees at Perusahaan XXX Banten. The sampling technique used was purposive sampling. Findings: The results of the study explain that employee placement has a positive and significant effect on employee performance,while training and organizational culture have a positive but not significant effect on employee performance at Perusahaan XXX Banten Banten